Making the invisible visible: results of a community-led health survey following PFAS contamination of drinking water in Merrimack, New Hampshire - Bindu Panikkar; Benjamin Lemmond; Laurene Allen; Carol DiPirro; Shaina Kasper (BMC, 2019)
Abstract Background In March 2016, citizens of Merrimack, New Hampshire, learned that their public water supply was contaminated with perfluorooctanoic acid (PFOA). A subsequent state-led investigation revealed widespread contamination of both public and private well water with PFOA and several related chemicals, broadly termed per- and polyfluoroalkyl substances (PFAS). This research examines the local response to PFAS contamination of the public water system and well water in Merrimack and the results from the health survey administered by a local advocacy group, Merrimack Citizens for Clean Water (MCFCW). Methods MCFCW designed and implemented a community health survey (n = 596) representing 213 households exposed to PFAS through drinking water. The surveys were conducted in the summer of 2017. Respondents used an online survey platform to report demographic information, exposure sources, and health conditions. Logistic regression was used to analyze the community-based health survey results . Results There were several important associations that warrant further investigation and more immediate attention, especially: 1) elevated incidence of developmental, autoimmune and kidney disorders among those under 18 years of age; 2) elevated levels of health concerns, multiple health concerns, autoimmune disorders, and reproductive disorders among women, 3) elevated levels of health concerns, multiple health conditions, cardiovascular, respiratory, reproductive, and liver disorders in those with industrial occupational exposures, and; 4) elevated incidence of health concerns, cardiovascular, and developmental disorders among those who have been living in Merrimack for a long time versus newer residents. Conclusions The limitations inherent in the study design warrant caution in interpreting the results, however the associations found in this study merit further investigation. This health survey highlights foremost the critical gap in information-lack of access to blood testing, medical monitoring and physician guidance of PFAS-exposed residents. This study provides a model for conducting community-based health studies to advocate for pathways to state supported biomonitoring and medical monitoring for those exposed to industrial toxins and to take into consideration the human health burden in shaping the future of chemical regulation.